The geography of despair among 15-44-year-old men in England and Wales: putting suicide on the map - Middleton, Nicos; Sterne, Jonathan Ac C C; Gunnell, David J. (My University, 2006)
Objective: To investigate the spatial patterning and possible contributors to the geographical distribution of suicide among 15-44- year-old men. Design: Small-area analysis and mapping of geo-coded 1988-94 suicide mortality data and 1991 census data using random-effects smoothing. Setting: 9265 electoral wards in England and Wales (mean population of men aged 15-44- years: about 1220). Main results: Two main patterns emerged: (a) in all of the 10 most densely populated cities studied, suicide showed a "bull's-eye" pattern with rates highest in the inner-city areas and, in some cases, low rates in the peripheries, and (b) suicide rates were high in coastal areas, particularly those in more remote regions. Possible indicators of social fragmentation, such as the proportion of single-person households in an area, were most strongly and consistently associated with rates of suicide in both urban and rural areas. Levels of unemployment and long-term illness accounted for some of the coastal patterning. Although characteristics of areas accounted for more than half of the observed variability, substantial between-area variability in rates remained unexplained. Conclusions: The area characteristics investigated here did not fully account for the higher suicide rates observed in the most rural or remote areas. Alongside social and economic aspects, rural life itself may have an independent effect on the risk of suicide. A greater understanding of local geographies of suicide, and particularly the possible interactions between characteristics of people and their environments, might assist the design of prevention strategies that target those areas (and their characteristics) where risk is concentrated.
Keywords: Adolescence; Demography; Maps; Suicide; Despair